Director networks and initial public offerings - Feng, Yi; Song, Keke; Tian, Yisong S. (Journal of Banking & Finance, 2019)
We investigate how director networks impact IPO characteristics and find that firms with better-connected directors have higher IPO market valuation, more positive offer price revisions, higher first-day returns, more pre-IPO media coverage, and superior post-IPO stock performance. Director networks are beneficial to the share offering because corporate directors help facilitate information exchange with prospective investors, attract their attention to the IPO, and maintain and grow their interest after the IPO.